Factors Affecting The Survival Trend In Carcinoma Stomach- A Hospital Based Study - Sarker, MK; Sarker, MM; Parveen, NA; Basak, PM; Raihan, ASMA (TAJ: Journal of Teachers Association, 2018)
Stomach cancer is a gastrointestinal malignancy with insidious onset and poor prognosis. The disease predominantly affects the older age groups with pick incidence between 60 to 70 years of age. The total number of stomach cancer patients available for the study within the stipulated time was 105. Among them 69.52% patients were male and 30.48% patients were female. 0.95% patient belonged to age group <20, 11.43% belonged to age group 21-30, 09.52% belonged to age group 31-40, 23.81% belonged to age group 41-50, 28.57% belonged to age group 51-60, 20.0% belonged to age group 61-70 and 05.72% patients were >70 years of age. Mean age was 54.91 years ± 13.42 SD. In our study, 45.6% survived <3 months, 15.8% 4–6 months, 07.0% 7–9 months, 14.0% 10–12 months, 10.6% 13–24 months and 07.0% >24 months. Among 57 expired patients, 14 got curative treatment and rest of 43 got palliative treatment. Those who got curative treatment, 36.4% survived 10–12 months, 45.5% 13–24 months and 18.1% > 24 months. Those who got palliative treatment 51.5% survived <3 months, 24.2% 4–6 months, 12.1% 7–9 months, 09.1% 10–12 months and 03.1% 13–24 months. Overall median survival was 06 months, for curative treatment 16 months and for palliative treatment 03 months. TAJ 2014; 27(2): 44-49